Invasive alien species observations and issues from around the world - Pullaiah, T.; Ielmini, Michael R. (Wiley-Blackwell, 2021)
"Invasive alien species (IAS), introduced intentionally or inadvertently, are one of the main drivers of global environmental change and cause significant ecological and economic damage. IAS threaten biosecurity, human and animal health, ecosystem services and important social aspects of cultures and communities on every continent. Underserved and marginalized peoples are at great risk from alien species invasions. The issue is a global crisis of enormous proportion and has grown insidiously for decades, exacerbated by the globalization of world economies and increased trade and travel. Globally, the concern for IAS varies greatly from nation to nation, and often lacks the level of conscious proactivity necessary to effectively address the threats before they are insurmountable. This is largely due to capacity limitations for most nations and is aggravated by shortage of funds to implement strategies, lack of policies, and variable levels of public awareness and perspectives on risk. Most importantly, IAS is yet to emerge as a priority issue to tackle for most countries although there are some changes visible now. The spread of a novel coronavirus (COVID-19), has rocketed the global biosecurity issue to a new level of consciousness, and perhaps galvanizing the world about the importance of disease pandemics and demonstrating that the IAS threat has so many parallel aspects of risk and spread. Through this publication, we attempt to compile information for a better understanding of the global threat of IAS, the diverse array of issues resultant of invasion, and considerations by decision makers for management. It shares information from every continent on the planet. We also attempt to provide a variety of perspectives, problems, solutions, and considerations relevant to invasions, and help illustrate how a large portion of world nations, cultures, communities, and organizations are struggling with the same issues as their neighbors do against the IAS threat. It thus becomes necessary to highlight the IAS threat in terms of a global 'call to action' at multiple scales and challenge the world to unify and collaborate at all levels"--